2018
DOI: 10.1093/infdis/jiy660
|View full text |Cite
|
Sign up to set email alerts
|

High Constitutive Interleukin 10 Level Interferes With the Immune Response to Varicella-Zoster Virus in Elderly Recipients of Live Attenuated Zoster Vaccine

Abstract: Introduction Live attenuated zoster vaccine (Zostavax) was used to test the hypothesis that constitutive level of interleukin 10 (IL-10), which may be high in elderly subjects, impairs vaccine efficacy. If constitutive IL-10 impairs vaccine efficacy, the effectiveness of viral vaccines might be improved by transient inhibition of IL-10 before vaccination. Methods Zostavax was given to 26 patients (age, 60–80 years). IL-10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
2
3
1
Order By: Relevance
“…IL‐10 secreted by PBMCs following LPS treatment at baseline was the one other parameter associated with post‐vaccination VZV responses. Our data are not in line with other studies that showed that high constitutive levels of IL‐10‐impaired live‐attenuated VZV vaccine immunogenicity, identified by an inverse relationship between IL‐10 and VZV response in elderly adults aged 60–80 years [33]. In addition, similar findings were reported from a cohort of older adults aged 63–85 years who were vaccinated against influenza, where high PHA‐induced IL‐10 production by leucocytes was associated with a low response to the vaccine [34].…”
Section: Discussioncontrasting
confidence: 99%
“…IL‐10 secreted by PBMCs following LPS treatment at baseline was the one other parameter associated with post‐vaccination VZV responses. Our data are not in line with other studies that showed that high constitutive levels of IL‐10‐impaired live‐attenuated VZV vaccine immunogenicity, identified by an inverse relationship between IL‐10 and VZV response in elderly adults aged 60–80 years [33]. In addition, similar findings were reported from a cohort of older adults aged 63–85 years who were vaccinated against influenza, where high PHA‐induced IL‐10 production by leucocytes was associated with a low response to the vaccine [34].…”
Section: Discussioncontrasting
confidence: 99%
“…This was also previously reported for hepatitis B with the live-attenuated zoster vaccines. 32,33 Notably, similar to our findings, the induction of antibodies measured by the fluorescence-antibody-to-membrane-antigen (FAMA) assay, which are associated with protection, was particularly inhibited compared with the antibodies measured by IgG-ELISA. Like the influenza HI-assay, the FAMA assay uses viral surface antigens that are conformationally specific and intact and therefore measures antibodies that have virus neutralization potential.…”
Section: Discussionsupporting
confidence: 87%
“…The recombinant VZV gE protein is co-formulated with the novel ASB01 adjuvant to induce both a strong CD4+ T cell and gE-specific antibody response (6,27). VZV-specific CD4+ T cell responses are associated with positive vaccine outcomes (20,54,59,62). The reasons for the remarkable difference in Shingrix efficacy may involve a capacity for eliciting a stronger and/or more focused response against the gE antigen, a broader epitope repertoire or an intrinsic difference in the quality and durability of the responses elicited.…”
Section: Introductionmentioning
confidence: 99%